Writing for publication group: professional development situated in the interstices of academia and performativity. Issue 4 (3rd July 2016) - Reyes, Vicente; Masters, Yvonne; Clary, Deidre; Betlem, Elisabeth C.; Jones, Marguerite A.; Charteris, Jennifer; Kivunja, Charles; Rizk, Nadya; Sigauke, Aaron
Abstract: This article features nine 'narratives of experience' illustrative of academics engaged in an alternative Professional Development (PD) activity, referred to as Writing for Publication, in a regional Australian university. Each narrative adopts a critical stance to academic practice situated in what Ball defines as a 'culture of performativity' perpetuated by a 'global neoliberal environment'. Contrary to professional development built primarily around sporadic content-provision and credential-based activities, Writing for Publication represents an alternative approach to professional development, a loose-coupling model, that gives validation to academics engaged in navigating dominant neoliberal discourses driving higher education filtered through the interstices or sites for identity-creation, agency formation and emerging communities of practice.